Coastal Ecosystem Restoration Based on "Good Governance": Case Study Gresik and Malang Regency, East Java Province - Rudianto Rudianto; Edi Susilo; Ade Yamindago (Research Journal of Life Science, 2015)
This study is focused on the institutional aspects as an essential prerequisite to the integration efforts of the coastal ecosystem restoration in Gresik and Malang regency. The purpose of this study was to perform coastal restoration with a "good governance" focus as a means of coastal restoration.The method to be used is to use Interpretive Structural Modeling (ISM) and Analytical Hierarchy Process (AHP). ISM is an interactive design methodology to develop structures that describe the relationship between elements. While AHP is a framework for effective decisions on complex problems.The results of this study is to show the formulation of the seven (7) priority structure. While the master plan drawn up leading to the respective roles of the stakeholders at the village level, district level, district level and provincial and national levels. While the preparation of the action plan was drawn up with reference to the 9 (nine) step restoration management in an integrated manner.